Computational identification of biologically functional non-hairpin GC-helices in human Argonaute mRNA - Dornseifer, Simon; Sczakiel, Georg (BMC bioinformatics, 2013)
Background Perfectly formed duplex elements in RNA occur within folding units, often as a part of hairpin motifs which can be reliably predicted by various RNA folding algorithms. Double helices with consecutive Watson-Crick base-pairing may also be formed between distant RNA segments thereby facilitating long-range interactions of long-chain RNA that may be biologically functional. Here we addressed the potential formation of RNA duplex motifs by long-range RNA-RNA interactions of distantly located matching sequence elements of a single long-chain RNA. Results We generated a Python-based software tool that identifies consecutive RNA duplex elements at any given length and nucleotide content formed by distant sequences. The software tool, dubbed RNAslider , is built on the theoretical RNA structure prediction algorithm Mfold. Source code and sample data sets are available on demand. We found that a small ratio of human genes including the Argonaute (Ago)-like gene family encode mRNAs containing highly GC-rich non-hairpin duplex elements (GC-helix) of equal to or more than 8 base pairs in length and we provide experimental evidence for their biological significance. Conclusion GC-helices are observed preferentially within the 5 ′ -region of mRNAs in an evolutionarily conserved fashion indicating their potential biological role. This view is supported experimentally by post-transcriptional regulation of gene expression of a fusion transcript containing 5 ′ -sequences of human mRNA Ago2 harbouring GC-helices and down-stream coding sequences of Renilla luciferase.